A new species of karst dwelling Cyrtodactylus (Squamata: Gekkonidae) from northwestern Laos - Schneider, Nicole; Nguyen, Truong Quang; Schmitz, Andreas; Kingsada, Phouthone; Auer, Markus; Ziegler, Thomas (Zootaxa, 2011)
We describe a new species of the gekkonid genus Cyrtodactylus from northwestern Laos, based on a recent collection from Vientiane Province. Cyrtodactylus pageli sp. n. is distinguished from the remaining bent-toed-geckos by the combination of the following characters: snout-vent length up to 81.8 mm; 9–12 supralabials; 9 infralabials; 9–14 rows of dorsal tubercles; no distinct lateral body fold; 41–46 midbody ventrals; precloacal pores present in both sexes (males 4, females 5 or 6); no precloacal groove; femoral scales not distinctly enlarged; no femoral pores; subdigital lamellae under the fourth toe 19–26; subcaudals transversally enlarged; dark nuchal band, followed by a transversal row of dark neck blotches (rarely forming an additional transversal neck band) in-between nuchal band and first body band; 5 in part irregular dark dorsal bands between limb insertions plus transversal band between hind limbs; tail with banded pattern.